Possible epigenetic role of vitexin in regulating neuroinflammation in Alzheimer’s disease - Yahaya, Muhamad Afiq Faisal; Zolkiffly, Siti Zaidathul Iman; Mohd Moklas, Mohamad Aris; Abdul Hamid, Hafizah; Zainol, Murizal; Mehat, Muhammad Zulfadli (Hindawi, 2020)
Alzheimer’s disease (AD) has been clinically characterized by a progressive degeneration of neurons which resulted in a gradual and irreversible cognitive impairment. The accumulation of Aβ and τ proteins in the brain contribute to the severity of the disease. Recently, vitexin compound has been the talk amongst researchers due to its pharmacological properties as anti-inflammation and anti-AD. However, the epigenetic mechanism of the compound in regulating the neuroinflammation activity is yet to be fully elucidated. Hence, this review discusses the potential of vitexin compound to have the pharmacoepigenetic property in regulating the neuroinflammation activity in relation to AD. It is with hope that the review would unveil the potential of vitexin as the candidate in treating AD.